Gate commutated thyristor with voltage independent maximum controllable current - Lophitis, Neophytos; Antoniou, Marina; Udrea, Florin; Nistor, Iulian; Rahimo, Munaf T.; Arnold, Martin; Wikstroem, Tobias; Vobecky, Jan (My University, 2013)
In this letter, we use a novel 3-D model, earlier calibrated with experimental results on standard gate commutated thyristors (GCTs), with the aim to explain the physics behind the high-power technology (HPT) GCT, to investigate what impact this design would have on 24 mm diameter GCTs, and to clarify the mechanisms that limit safe switching at different dc-link voltages. The 3-D simulation results show that the HPT design can increase the maximum controllable current in 24 mm diameter devices beyond the realm of GCT switching, known as the hard-drive limit. It is proposed that the maximum controllable current becomes independent of the dc-link voltage for the complete range of operating voltage. © 1980-2012 IEEE.
Keywords: Gate commutated thyristor; maximum controllable current; safe operating area; thyristor; wafer modeling